2017
DOI: 10.1111/1365-2435.12873
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical influences of prey distribution on patterns of prey capture by a marine predator

Abstract: Summary Prey distribution acts at multiple spatial scales to influence foraging success by predators. The overall distribution of prey may shape foraging ranges, the distance between patches may influence the ability of predators to detect and move between profitable areas, and individual patch characteristics may affect prey capture efficiency. In this study, we assessed relationships between spatially explicit patterns of prey capture by a central place forager, the little penguin (using GPS tracking and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 55 publications
1
54
0
Order By: Relevance
“…Foraging performance of breeding seabirds has been linked to chick condition (Horswill, Trathan, & Ratcliffe, 2017;Pinaud, Cherel, & Weimerskirch, 2005), reproductive success (Dee Boersma & Rebstock, 2009;Piatt et al, 2007) and population growth (Lewis et al, 2006) yet, there are few data linking foraging performance and measures of prey availability concurrently (but see Boyd et al, 2015;Carroll et al, 2017). This study presents a unique account of functional relationships between seabird foraging performance and prey availability facilitated by a comparison between a representative sample of birds simultaneously deployed on survey days that spanned a temporal range of informative variation in prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…Foraging performance of breeding seabirds has been linked to chick condition (Horswill, Trathan, & Ratcliffe, 2017;Pinaud, Cherel, & Weimerskirch, 2005), reproductive success (Dee Boersma & Rebstock, 2009;Piatt et al, 2007) and population growth (Lewis et al, 2006) yet, there are few data linking foraging performance and measures of prey availability concurrently (but see Boyd et al, 2015;Carroll et al, 2017). This study presents a unique account of functional relationships between seabird foraging performance and prey availability facilitated by a comparison between a representative sample of birds simultaneously deployed on survey days that spanned a temporal range of informative variation in prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…The depth distribution of prey plays an important role in how predators use their habitat (Benoit‐Bird et al., ; Boyd et al., ; Carroll et al., ). By exploring the relationship between the number of PCE with dive depth and duration, we have shown that two species, guillemots and razorbills, clearly made different decisions while exploiting the water column.…”
Section: Discussionmentioning
confidence: 99%
“…In other diving marine predators (e.g., the little penguin (Eudyptula minor), Peruvian booby (Sula variegata), and Guanay cormorant (Phalacrocorax bougainvilliorum)), the distribution of prey capture events and dives in the water column match the local distribution of their prey (Boyd et al, 2016;Carroll et al, 2017). Therefore, we assumed that the number of PCE performed in each dive is a measure of foraging effort occurring in the presence of prey.…”
Section: Individual Dive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed records of prey abundance and distribution and accurate indices of feeding are difficult to obtain for the majority of species and although visual assessment of prey capture is possible for some species (Seminoff et al, 2006;Elliott et al, 2008), in most cases, indirect parameters have been used as a proxy (e.g., gastric or visceral temperature changes, mouth/beak opening or head/jaw movement, accelerometer signatures; Sepulveda et al, 2004;Gleiss et al, 2011aGleiss et al, , 2013Nakamura et al, 2011Nakamura et al, , 2015Carroll et al, 2014;Nakamura and Sato, 2014). For efficient foraging by predators, patterns of habitat use are assumed to reflect the distribution, density and quality of prey resources (Stephens and Krebs, 1986;Austin et al, 2006;Carroll et al, 2017). Therefore, horizontal and vertical movements of marine predators in addition to the frequency of dives, their persistence and other characteristics are expected to be related to distinct activities such as foraging or traveling (e.g., Horodysky et al, 2007;Thomson et al, 2011;Dragon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%